THE EFFECT OF THE WINGKOSMART EDUCATIONAL PLATFORM ON COMMUNITY KNOWLEDGE OF THE WOLBACHIA PROGRAM - Aerrosa Murenda Mayadilanuari; Silvia Nurvita; Siska Narulita (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Dengue hemorrhagic fever (DHF) remained a major public health issue in Semarang City, with 404 reported cases and 16 fatalities in 2023. To address this issue, the Wolbachia-based vector control program, WINGKO (Wolbachia Ing Kota Semarang), was introduced in 2023. However, public understanding of the program remained limited. This study aimed to evaluate the effectiveness of WINGKOSmart, a digital education platform, in improving community knowledge of the Wolbachia program. A quasi-experimental one-group pretest-posttest design was conducted from June to August 2025 in Muktiharjo Kidul Village, involving 30 purposively selected participants aged 18 to 59 years who were capable of using the internet. Data were collected using a validated 20-item questionnaire and analyzed using the Wilcoxon test. The results showed significant improvement in respondents’ knowledge after the intervention (p < 0.05). The proportion of respondents in the “good” knowledge category increased across all subgroups, with younger respondents (87.5%), females (92%), high school graduates (91.3%), and unemployed participants (90%) demonstrating the greatest improvements, while the “poor” knowledge category was eliminated. The study concluded that WINGKOSmart effectively improved community knowledge of the Wolbachia program and has strong potential as a digital-based health promotion strategy to support dengue control efforts in Semarang City. Keywords: dengue hemorrhagic fever, health education platform, Wolbachia DOI 10.35990/mk.v9n2.p127-136